Development of Report Turnaround Times in a University Department of Radiology during Implementation of a Reformed Curriculum for Undergraduate Medical Education - Albrecht, Liane; Maurer, Martin H.; Seithe, Tim; Braun, Joachim; Gummert, Richard; Auer, Jonas; Sponheuer, Keno; Meyl, Tobias Philipp; Hamm, Bernd; de Bucourt, Maximilian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose The implementation of a reformed curriculum for undergraduate medical education with a problem-oriented focus and more bedside teaching in small groups increases the academic teaching workload. The aim of this study was to investigate whether this increase in teaching duties is associated with an increase in report turnaround times of radiologists or increased unplanned absence during term times compared with term breaks (lecture-free periods) and over the whole period under investigation.Materials and Methods The database of all radiological examinations performed at a large German university hospital was retrospectively analyzed for a two-year period from the winter term 2011/12 to the summer term 2013. A total of 192 984 radiological examinations performed during this period were included in an analysis of reporting times (i. e., time from end of examination to completion of report) during term times versus term breaks. Reporting times were analyzed for all radiological examinations and for intensive care unit (ICU) patients. In addition, radiologists’ schedules were analyzed in terms of teaching duties, unplanned absence, vacation days, and days away from work for education and training.Results During the period under investigation, the teaching load increased from overall 1.75 hours/day in the winter term 2011/12 to 6.49 hours/day in the summer term 2013 and in the term break from overall 0.10 hours/day in the winter term 2011/12 to 0.71 hours/day in the summer term 2013. Reporting time increased during this period (p < 0.05) but remained shorter during term times than during term breaks. The difference between term and term break for ICU patients was not significant. There was no increase in unplanned absences during term times.Conclusion Overall, radiologists’ reporting times increased during the period when the reformed curriculum for undergraduate medical education was implemented. As this was observed both during term and during term breaks, increased teaching duties alone cannot serve as a sole causal explanation.Key Points:Citation Format
Keywords: turnaround time; workload; quality management; workflow analysis; reformed curriculum for undergraduate medical education